Social Cognition in Kompas Daily Editorials - Zustiyantoro, Dhoni; Halim Ali, Abdul; Amali, Zakki (Abjad Journal of Humanities & Education, 2023)
This article discusses social cognition in the Kompas Daily editorial using Teun A van Dijk's theoretical framework. Social cognition, as the central concept in this theory, refers to how individuals process, store, and use social information in various forms of communication. This research explores how Kompas daily editorials utilize the principles of social cognition in forming public opinions and views. This study uses the content analysis method to analyze the Kompas daily editorial "Listen to the Voice of the People", published on October 6, 2020. The results of the analysis show that there are social cognitive patterns that emerge in word choice, framing and editorial argumentation structure. Within the theoretical framework of Teun A van Dijk, this article explores how these editorials build social representations, manipulate collective cognition, and influence the process of people's understanding of specific issues. The findings from this research provide new insights regarding the use of social cognition in the context of mass media, especially daily editorials. The implications of the results of this research help further understanding of how mass media can play an essential role in shaping people's perceptions and attitudes towards social and political issues. This article also strengthens the argument that journalism is increasingly needed to build public awareness of policies.